Lost souls meet under a full moon - Tsujimura, Mizuki (Doubleday, 2025)
"A suspenseful magical realism novel about a mysterious teenage "Go-Between" who arranges meetings between the living and the dead, from multimillion copy Japanese bestselling author Mizuki Tsujimura"--